Oxidative stress-mediated responses in endometrial cancer cells: contrasting effects of doxorubicin and menadione - Kozak, Joanna; Tkaczyk–Beraś, Sandra; Jędraszek, Krzysztof (Frontiers in Physiology, 2026)
BackgroundOxidative stress plays a crucial role in the development and treatment response of endometrial cancer, yet the antioxidant defense mechanisms in different tumor subtypes remain unclear.MethodsWe investigated the cellular response to oxidative (menadione) and genotoxic (doxorubicin) stress in two TP53-mutated endometrial cancer cell lines, AN3CA and KLE. Cell viability, reactive oxygen species (ROS) levels, and the expression of antioxidant-related genes (SESN2, SESN3, SOD1) were assessed using qPCR and In-Cell Western assays.ResultsAN3CA cells showed greater sensitivity to doxorubicin, marked by increased ROS and reduced viability, while KLE cells were more susceptible to menadione-induced toxicity. Protein expression analysis revealed a biphasic response: low doses of doxorubicin transiently increased SESN and SOD1 expression, whereas higher doses suppressed them. Gene expression at the mRNA level did not always correlate with protein levels, suggesting possible post-transcriptional regulation.ConclusionOur findings demonstrate cell line - specific redox responses and identify SESN2, SESN3, and SOD1 as key players in the antioxidant defense network. These genes may serve as potential therapeutic targets in aggressive, hormone-independent endometrial cancers.